The discursive construction of Iran from 1979 to 2009 in the New York Times - Jahedi, Maryam (2012)
Critical Discourse Analysis (CDA) is a multidisciplinary approach to the analysis of language as discourse which focuses on the substantively linguistic and semiotic nature of social relations of power in contemporary societies. CDA is used to analyze texts in order to examine what structures, strategies, or other properties of language play a role in the (re)production of unequal power relations. Using a combination of analytical tools and approaches advocated by prominent scholars in the field of CDA, the study investigated the discursive features of The New York Times (The NYT) news media to highlight how discursive strategies, structures and related rhetorical devices were deployed to portray the Iranian nation and to provide insight into how the information presented in the news texts had ideological implications for geopolitical relations. The textual data of the study covered the period from the Islamic Revolution of Iran in 1979 to the events of 2009. The headlines and leads of news items were examined: (1) to identify which themes or topics were recurrent in the media about Iran; (2) to describe the discursive devices, structures, and strategies used in the corpora of the news about Iran; (3) to analyze linguistic means or forms that were employed; and (4) to uncover the ideologies about the Iranian nation which seem to underlie its discursive representation. The results of The NYT news discourse analysis showed that the predominant themes about Iran centered on the concepts of violence and threat (to other nations). Discursive strategies such as referential strategies, predication strategies and argumentation strategies were employed to promote these ideological themes on the portrayal of prominent Iranian social actors. The discursive analysis showed that there was a tendency to polarize between Us (good, righteous,peaceful, etc.) and Them (evil, violent, etc.) to associate stereotypical negative traits to the out-group. The study found that such ideological representations of the Iranian participants were linguistically realized via the dominant processes of transitivity, thematization, and lexicalization. The net effect of the discourse themes, strategies and their associated linguistic means of realization in the stereotypical construction of Iran in The NYT was that of the negative Other, a nation of people that formed part of George W. Bush’s contentious “axis of evil”– evil, untrustworthy, violent, and a threat to world peace. The findings of the study are expected to further illuminate our understanding of powerful role of dominant international news media discourse in (re)producing unequal power relations and the discursive construction of an entire society in geopolitically negative terms to skew world opinion against it. In this way, the study contributes not only to the field of critical discourse studies but also to the related disciplines of journalism, international communication studies, and foreign affairs, among others.